Hubungan Self Care Management Diabetes dengan Kualitas Hidup Pasien Diabetes Mellitus Tipe - Wa Ode Sri Asnaniar; Safruddin Safruddin (FORIKES, 2019)
Self care is one of the nursing theories which is a form of increasing client independence so that clients can function optimally. This study aims to analyze the relationship of self care with the quality of life of patients with Type 2 Diabetes Mellitus in Antang Health Center, Makassar City. The design of this study is a quantitative study with a cross-sectional study design. The population in this study were patients with Type 2 diabetes mellitus at the Antang Health Center in Makassar City. The number of samples was 38 people using total sampling technique. Data analysis used Chi-Square test with a significance level of α = 0.05. The results showed that patients with type 2 diabetes mellitus in Antang Health Center who had Self care management had good diabetes as much as 16% while self care was less than 22%. Type 2 Diabetes Mellitus patients in Antang Health Center who have high quality of life are 39.5% and the quality of life is as low as 60.5%. Statistical tests obtained p value (0,000)